Bimbingan Terstruktur Terbatas dalam Pembelajaran Jarak Jauh untuk Meningkatkan Partisipasi Belajar Siswa SMA Negeri 2 Bayan - Moch Fatkoer Rohman (Jurnal Paedagogy, 2021)
This study aims to increase student participation through limited structured guidance in distance learning at SMA Negeri 2 Bayan. This research method used school action research with the stages of planning, action, observation and reflection which consists of 2 cycles. The instruments used were questionnaires and documentation. The data analysis technique used in this research was qualitative and quantitative descriptive analysis. The results showed that in the pre-cycle, learning participation was very low, namely only 5%, (less) in the first cycle of 41% (less) and in the second cycle of 51% (sufficient). The quality of guidance in the first cycle was 74 (enough) while in the second cycle it was 84% (good). So that the results of this study can be concluded that limited structured guidance can increase student participation in SMA Negeri 2 Bayan.